2007
DOI: 10.1158/1055-9965.epi-06-0823
|View full text |Cite
|
Sign up to set email alerts
|

The UDP-Glucuronosyltransferase 2B17 Gene Deletion Polymorphism: Sex-Specific Association with Urinary 4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanol Glucuronidation Phenotype and Risk for Lung Cancer

Abstract: 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone is a potent and abundant procarcinogen found in tobacco smoke, and glucuronidation of its major metabolite, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), by UDP-glucuronosyltransferases (UGT) including UGT2B17 is an important mechanism for 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone detoxification. Both copies of the UGT2B17 gene are deleted in f10% of Whites and the deletion is associated with a reduction in NNAL glucuronidation activity in vitro. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 33 publications
(48 reference statements)
5
85
1
2
Order By: Relevance
“…All UGT2B isoforms were detected in all human liver tissue specimens examined, as previously reported by other groups (Nakamura et al, 2008a;Izukawa et al, 2009;Ohno and Nakajin, 2009;Court et al, 2012). Only UGT2B17 exhibited no expression in four of the liver specimens examined, likely because those specimens were from subjects exhibiting the homozygous genotype for the prevalent (30% in Caucasians) UGT2B17 wholegene deletion allele (Wilson et al, 2004;Lazarus et al, 2005;Gallagher et al, 2007). The relative levels of hepatic expression were highest for UGT2B4, followed by UGT2B7 .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…All UGT2B isoforms were detected in all human liver tissue specimens examined, as previously reported by other groups (Nakamura et al, 2008a;Izukawa et al, 2009;Ohno and Nakajin, 2009;Court et al, 2012). Only UGT2B17 exhibited no expression in four of the liver specimens examined, likely because those specimens were from subjects exhibiting the homozygous genotype for the prevalent (30% in Caucasians) UGT2B17 wholegene deletion allele (Wilson et al, 2004;Lazarus et al, 2005;Gallagher et al, 2007). The relative levels of hepatic expression were highest for UGT2B4, followed by UGT2B7 .…”
Section: Resultssupporting
confidence: 80%
“…With the exception of human tongue, UGT2B17 was expressed at the highest or second-highest level of any of the UGT2B genes. UGT2B17 exhibits the highest activity of all UGTs in forming the O-glucuronide of NNAL (Lazarus et al, 2005), and the UGT2B17 gene deletion is associated with lung adenocarcinoma risk (Gallagher et al, 2007), a pattern consistent with the high levels of UGT2B17 expression observed in lung in the present study and with NNAL's induction of lung adenocarcinoma in rodent models (Rivenson et al, 1988;Hecht, 1998). While no studies have examined the role of the UGT2B17 deletion in cancer susceptibility within the aerodigestive tract, relatively high levels of UGT2B17 expression in larynx, tonsil, esophagus, and floor of mouth suggests that the UGT2B17 deletion may play a similarly important etiologic role in the induction of cancers within these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…12 It also has been reported that polymorphisms in the phase II conjugation enzyme genes, such as uridine diphosphate glucuronosyltransferase 1 family, polypeptide A7 (UGT1A7) and UGT2B17, have implications in lung cancer etiology. 13,14 However, few studies have addressed the relation between genetic predisposition to lung cancer and polymorphisms in phase III transporter genes.…”
mentioning
confidence: 99%
“…Pharmacogenetic variability in XMEs can impact their role in the overall disposition of drugs and xenobiotics, and may predict the clinical outcome. An example is the UGT2B17 gene deletion, which was found to correlate with increased incidence of lung adenocarcinoma in women, possibly due to decreased glucuronidation (detoxification) of the tobacco-specific carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (Gallagher et al, 2007).…”
Section: Pulmonary Metabolism Of Resveratrol: In Vitro and In Vivomentioning
confidence: 99%
“…The key P450, UGT, SULT, and drug transporters known to be expressed in the human lung are depicted (PEPT, peptide transporter; SLCO, solute carrier organic anion transporter; OATP, organic anion-transporting polypeptide). Data compiled from previously published reports (Gallagher et al, 2007;Somers et al, 2007;Bosquillon, 2010;Anttila et al, 2011;Sharan and Nagar, 2013;Jones and Lazarus, 2014).…”
Section: Pulmonary Metabolism Of Resveratrol: In Vitro and In Vivomentioning
confidence: 99%